Circulating Microparticles: A risk factor for recurrent abortion in women at the University Teaching Hospital - Chibuye, Sylvia (Lusaka: University of Zambia, 2016)
Spontaneous abortion in Zambia is defined as non induced embryonic death or passage of products of conception before 28 weeks' gestation. Placental insufficiency as a result of thrombi lodging in the uteroplacental bed is considered to be a cause of pregnancy loss. Circulating microparticles are minute sized particles associated with prothrombotic nature and have been found to be increased in the uteroplacental circulation in pregnancy.
Thesis--(Msc .)-- University of Zambia, 2016.
Includes bibliographical references.
Keywords: Abortion, Habitual